House prices, home equity, and personal debt composition - Jieying Li; Xin Zhang (Sveriges Riksbank, 2017)
Using a monthly panel dataset of individuals' debt composition including mortgage and nonmortgage consumer credit, we show that house price changes can explain a significant fraction of personal debt composition dynamics. We exploit the variation in local house price growth as shocks to homeowners' housing wealth to study the consequential adjustment of personal debt composition. To account for local demand shocks and disentangle the housing collateral channel from the wealth effect, we use renters and non-equity-withdrawal homeowners in the same region as control groups. We present direct evidence that homeowners reoptimize their debt structure by using withdrawn home equity to pay down comparatively expensive short-term non-mortgage debt during a housing boom, unsecured consumer loans in particular. We also find that homeowners withdraw home equity to finance their entrepreneurial activities. Our study sheds new light on the dynamics of personal debt composition in response to changes in house prices.
Keywords: D14; G21; L26; R31; 330; Household Decision; Personal Debt Management; Credit Constraint; Cash-out Refinancing; Entrepreneurship